Introduction to game design, prototyping, and development : from concept to playable game with Unity and C# - Bond, Jeremy Gibson (Addison-Wesley, 2018)
"This guide illuminates the basic tenets of game design and presents a detailed, project-based introduction to game prototyping and development, using both paper and the Unity game engine. Jeremy Gibson presents prototyping as a core game design skill (much as sketching is a core artist's skill), taking a straightforward, commonsense approach that has been refined over many years of teaching beginners. Throughout, students are encouraged to experiment on their own, and to discover that most problems have multiple solutions"--Provided by publisher